Moose foraging patterns : implications for the use of browsing indices - Lindqvist, Sara (SLU/Dept. of Ecology, 2012)
ABSTRACT Moose (Alces alces) foraging on young Scots pine (Pinus sylvestris) might reduce economical profit in forestry due to deteriorated log quality and biomass loss. Different indices are used to quantitatively estimate browsing effect on this tree species. I wanted to compare the relationship between two commonly applied survey methods for assessing browsing: the Moose Damage and the Browsing Pressure surveys. Furthermore a variety of factors influencing browsing intensity have been identified, yet moose selectivity for apical or lateral shoots of Scots pine has never been tested. Data on damage and browsing pressure was collected in young Scots pine stands (n=60 stands) within the southern boreal zone in Sweden. Logistic models were fitted to test the relationship between the indices and other factors possibly influencing the relation: pine density and mean stand height. Moose browsed the same relative proportions of apical and lateral shoots in relation to availability and there was no significant difference in selectivity towards either of the shoot categories, suggesting that moose forage shoots proportionally to what is available. The relationship between the two browsing indices was significant but the fit was not statistically perfect. Damage and browsing pressure most often coincided but browsing pressure did not always equate to stem damage. The Moose Damage survey could be used in favor of Browsing Pressure survey although both pine density and mean stand height also significantly affected the relationship between the methods. Hence using stem damage to predict browsing pressure (and vice versa) should be done with caution.